Sustainable transportation planning - Tumlin, Jeffrey; ProQuest (Firm) (Hoboken, N.J. : Wiley, 2011)
"As transportations-related disciplines of urban planning, architecture, landscape architecture, urban economics, and social policy have undergone major internal reform efforts in recent decades Written in clear, easy-to-follow language, this book provides planning practitioners with the tools they need to achieve their cities' economic development, social equity and ecological sustainability goals. Starting with detailed advice for improving each mode of transportation, the book offers guidance on balancing the needs of each mode against each other, whether on a downtown street, or a small town neighborhood, or a regional network"--
Includes bibliographical references and index.
Electronic reproduction. Ann Arbor, MI : ProQuest, 2015. Available via World Wide Web. Access may be limited to ProQuest affiliated libraries.
Keywords: Transportation -- Planning; Sustainable urban development; Electronic books